2017
DOI: 10.2147/dmso.s131340
|View full text |Cite
|
Sign up to set email alerts
|

Do we need to measure vitamin B12 and magnesium in morbidly obese patients with type 2 diabetes mellitus?

Abstract: ObjectiveWe aimed to investigate the prevalence of B12 deficiency in metformin-treated, morbidly obese, type 2 diabetes mellitus (T2DM) patients, compared to morbidly obese controls, as well as to evaluate the magnesium status.DesignRetrospective cross-sectional analysis of plasma vitamin B12, plasma magnesium, glucometabolic status and clinical measurements in all consecutive morbidly obese patients was conducted during 1 year.SettingOutpatient Clinic of Obesity Care.SubjectsOne hundred forty-seven patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…By contrast, metformin did not significantly change serum Mg levels, leading to significantly lower levels than the control. Our results are in accordance with the findings of previous studies (Chakraborty et al, 2011, Wahlen et al, 2017. Even though the glibenclamide treated group in the present study had worse glycaemic control, they showed better serum Mg levels than the patients treated with metformin.…”
Section: Metforminsupporting
confidence: 93%
“…By contrast, metformin did not significantly change serum Mg levels, leading to significantly lower levels than the control. Our results are in accordance with the findings of previous studies (Chakraborty et al, 2011, Wahlen et al, 2017. Even though the glibenclamide treated group in the present study had worse glycaemic control, they showed better serum Mg levels than the patients treated with metformin.…”
Section: Metforminsupporting
confidence: 93%
“…Additionally, Swedish researchers recommend that to optimally benefit from medication with metformin, morbidly obese patients should undergo routine assessments of both vitamin B 12 and magnesium levels, with relevant supplementation considered where necessary to maintain optimal status. 190 As detailed earlier in this review, the recommendation that calcium supplementation could potentially prevent metformin-induced deficiency of vitamin B 12 is premature due to the existing paucity of studies. 59…”
Section: Clinical Issues Around Metformin Use and Vitamin B 12 Statusmentioning
confidence: 98%
“…104,150,151 Patients who are prescribed metformin should therefore be monitored periodically and, if appropriate, provided vitamin B12 supplements, especially if the patients have other co-existing conditions such as renal or hepatic impairment. 151,152 Metformininduced vitamin B12 deficiency has been linked to higher frequencies of autonomic neuropathy and linked to a 3.16 fold increase in cardiovascular events, including cardiac arrhythmias, and a 3.17 fold increase in mortality and therefore of importance when considering the chronic use of metformin in subjects with AF. 149,153 Metformin is predominantly cleared by the kidneys thereby requiring that the dosage should be adjusted if the patient has reduced renal function.…”
Section: Putative Mechanisms Of Action Of Metformin and Concerns Over...mentioning
confidence: 99%